The Death Knock. - Chaplin, Kathleen (New England Review (10531297), 2013)
The article presents the author's testimony concerning the aspects of the death knock. She outlines several Irish death omens including a loud crashing noise, fire, and an infestation of foxes. She notes that the accounts of the death knock tend to comprise few sentences with the same basic content. She opines that most accounts of the knock end with the revelation of the death, not with the experience's meditation.